Clinical characteristics, morbidity, and prognostic value of concomitant coronary artery disease in idiopathic dilated cardiomyopathy - Frankenstein, Lutz; Hees, Henrik; Täger, Tobias; Fröhlich, Hanna; Dösch, Andreas; Cebola, Rita; Zugck, Christian; Katus, Hugo (Clinical research in cardiology, 2013)
Patients with idiopathic dilated cardiomyopathy (dCMP) might present coronary artery disease (CAD) concomitant to dCMP and prognostic differences between ischemic heart disease and non-ischemic cardiomyopathy have been described. Clinical characteristics and prognostic implications of concomitant CAD in patients with dCMP are largely unknown.
Gesehen am 30.04.2021